Methods to Increase the Efficiency of Placement of Financial Resources of Insurance Companies - Kenjaev Giyozovich, Ilhom; Khattabov Botirovich, Murodulla (International Journal of Psychosocial Rehabilitation, 2020)
The article provides an analysis of the quality and efficiency of the placement of financial resources of insurance companies, as well as proposals and recommendations to improve the efficiency of the placement of financial resources of insurance companies.